Law Enforcement Against the Eradication of Thuggery in Brimob Company 2, Battalion A, Buntu Bedimbar Village, Tanjung Morawa District, Deli Serdang Regency - Abdul Muharram Henry; Herlina Hanum Harahap (Yayasan Adra Karima Hubbi, 2025)
Background. The phenomenon of thuggery in Indonesia, particularly in Deli Serdang Regency, continues to grow, even amidst increasingly difficult economic conditions and rising unemployment. These ongoing incidents of thuggery seriously disrupt public order and security. Objective. The aim of this research is to provide a general overview of the police's efforts in maintaining public security and order, enforcing the law, and providing protection, maintenance and services to the community in order to maintain security. Method. The research method used in this thesis is empirical legal research. Empirical legal research can also be called sociological legal research and field research. Sociological legal research is based on primary data. Results. Law enforcement against thuggery in the Mobile Brigade Unit 2, Battalion A, Buntu Bedimbar Village, Tanjung Morawa District, Deli Serdang Regency, has been adjusted to the substance of the Criminal Code (KUHP) itself. Because thuggery refers to several acts, it will be processed based on the crimes committed. Conclusion. Law enforcement against thuggery still faces obstacles. These obstacles include: Internal and External constraints, such as inadequate facilities and infrastructure, disrupted information networks, a lack of evidence and witnesses, and public apathy in assisting the police.